Pussy envy: towards post-colonial agencies of feminine corporeality - Hoo, Regina Lei Kim (2024)
Since Independence, the Malay-Muslim woman’s body has been the site of various discursive contests imposed onto her personhood as a consequence of the conflict between the state and religious “dakwa” movement, and later, their alliance. Significantly, these changes have displayed a contradiction. On one hand, it has been made permissible on account of the Malay woman’s active acquiescence, in aspiring to the paradigm of “ideal” Muslim womanhood and its moral and familial obligations. On the other hand, various studies have documented the different layers of resistance to Islamic heteropatriarchal hegemony that Malay women exhibited through cultural and informal means.